Revitalisasi Fungsi Masjid Dalam Mengatasi Anomi Masyarakat Muslim Indonesia di Era Industrialisasi - Aisy, Nurul; Hidayat, Tatang; Istianah, Istianah (Hadara : Journal of Da'wah and Islamic Civilization, 2025)
One of the problems that afflicts industrialized societies today is that they are infected with anomy or symptoms of alienation. This causes many Muslims to no longer feel part of the ummah. The purpose of this study is to analyze the revitalization of the mosque function in overcoming the phenomenon of anomy in the Muslim community in the era of industrialization. The approach in the research is qualitative with a literature study method. Literature studied from the Qur'an, Hadith, Tafsir Books, Books, and journals. Data analysis uses descriptive analysis method. Based on the results of the study, anomy arises due to the phenomenon of urban life, which causes the younger generation to no longer gain religious knowledge from conventional institutions such as Islamic boarding schools, mosques, and madrasas, but only through the internet or social media. In overcoming these problems, the mosque plays an important role as the center of the Muslim community, which strengthens the social-psychological-intellectual bond, by carrying out its proper function. Thus, the mosque can act as a shield for the mental crisis to the solution to the decline of the ummah in various fields that are currently afflicting it.